PRIVATE PARTNERSHIP FOR PROTRACTED REFUGEES FROM MYANMAR - Sangfai, Boonshan (PEOPLE: International Journal of Social Sciences, 2018)
Some 100,000 people from Myanmar have been living in 9 refugee camps along the Thailand-Myanmar borderland which have been established for over 33 years. Media outlets report and portray multiple images and tales of implications and suffering from human insecurity in camp confinement for successive periods which has become one of the longest protracted refugee situations. There are three desirable durable solutions facilitated by UNHCR which are voluntary repatriation, resettlement and sustainable local integration which are now almost exhaustive. The continuation of open-ended confinement and limit their basic human rights have become wicked humanitarian challenges as if they were the forgotten people in confinement. This research concludes to broaden the role of other humanitarian actors, in particular, private sectors in the form of private partnership along the line with the concept of the UN Global Compact Policy; recommendation by world leaders in the World Economic Forum in Davos; UNHCR Policy of Partnership with private sectors and the Policy of Call to Action for private sectors for refugee crises by President Obama Administration. The concept of private partnership should be applied as a contemporary solution for protracted refugees from Myanmar which is, in turn, contribute to the economic growth in Thailand. This private partnership initiative may be considered as a pocket of hope and opportunities in the best interest of all stakeholders, in particular, the protracted refugees.